2023
DOI: 10.3390/plants12142694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single and Combined Drought and Salinity Stress on the Root Morphological Characteristics and Root Hydraulic Conductivity of Different Winter Wheat Varieties

Abstract: Water shortages and crop responses to drought and salt stress are related to the efficient use of water resources and are closely related to food security. In addition, PEG or NaCl stress alone affect the root hydraulic conductivity (Lpr). However, the effects of combined PEG and NaCl stress on Lpr and the differences among wheat varieties are unknown. We investigated the effects of combined PEG and NaCl stress on the root parameters, nitrogen (N) and carbon content, antioxidant enzymes, osmotic adjustment, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…Recently, it was shown that drought stress, salt stress, and dual drought-salt stress obviously reduced Lpr [19,21,69]. And root length/leaf area positively and significantly affected Lpr of Hengmai 4399, Yannong 1212, and Xinmai 19 under PEG and salt stress [21]. In this experiment, seed priming strongly improved root hydraulic conductivity of H4399, Y1212, and X19 under dual PEG and salt stress to enhance root water and ion uptake capacity (Figure 8).…”
Section: Seed-priming Using Melatonin Increasing Root Hydraulic Condu...mentioning
confidence: 55%
See 3 more Smart Citations
“…Recently, it was shown that drought stress, salt stress, and dual drought-salt stress obviously reduced Lpr [19,21,69]. And root length/leaf area positively and significantly affected Lpr of Hengmai 4399, Yannong 1212, and Xinmai 19 under PEG and salt stress [21]. In this experiment, seed priming strongly improved root hydraulic conductivity of H4399, Y1212, and X19 under dual PEG and salt stress to enhance root water and ion uptake capacity (Figure 8).…”
Section: Seed-priming Using Melatonin Increasing Root Hydraulic Condu...mentioning
confidence: 55%
“…However, research about the effects of melatonin on root hydraulic conductivity in wheat seedlings under drought, salt stress, and combined drought-salt stress is limited. In this study, similar to that of Fu et al [21], seeds of H4399, Y1212, and X19 pre-treated with melatonin were germinated under polyethylene glycol 6000 (PEG-6000), NaCl, and PEG-NaCl combined stress. And these seedlings were treated with stress in hydroponics.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The drought and salinity stresses caused a reduction in root hydraulic conductivity (Lpr), root length (RL), root surface area (RS), root volume (RV), K + and N content in shoots and roots of three different wheat varieties. In contrast, increased levels of antioxidant enzyme activity, malondialdehyde (MDA) levels, osmotic adjustment, nonstructural carbon, and Na + content were all observed in the shoots and roots [ 4 ]. Biotic stress adversely affects the health of wheat plant and lead to a significant reduction in the yield and quality of the grains produced.…”
Section: Introductionmentioning
confidence: 99%